Pest Management and Pesticides: A Historical Perspective - Frederick M. Fishel (EDIS)
PI219, a 6-page illustrated fact sheet by Frederick M. Fishel, provides a historical perspective on the impact of pests and pesticides on human society, including a chronological list of significant events involving pesticides. Includes references. Published by the UF Department of Agronomy, December 2009.